Ruling class, ruling culture studies of conflict, power, and hegemony in Australian life - Connell, Raewyn 1944- (Cambridge University Press, 1977)
This is a study of the Australian ruling class - the main companies, the leading political groups and the links and conflicts among them. The author also analyses class inequalities in education, the development of children's ideas about class, the role of the mass media and the way class relations are cemented culturally and psychologically. He introduces his book with a brief discussion of the literature on class theory, and a critical evaluation of Australian writing on class. Professor Connell's major aims are to describe and analyse Australia in the 1970s, to show how class theory is a useful tool in understanding the situation and to develop the theory by working through some practical cases. Apart from its obvious importance for Australian readers, this book should be of interest in other countries, both for comparison and for its original ideas on a number of important issues, such as conflict in the ruling class, and class consciousness in young people